The Use Of The Hellotalk Application To Improve Writing Skill In Recount Text - Anisa Septia Megawati; Chantika Dewi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
his research was about the use of the HelloTalk application to improve writing skill in recount text at ten grade of SMK Mutiara Terpadu Palabuhanratu Sukabumi. The objective of the research are to know (1) Is there any effectiveness in the use of the HelloTalk application improve writing skills in recount text at Tenth grade SMK Mutiara Terpadu Palabuhanratu? and (2) Is there any differences between students taught by using HelloTalk application and those are not at Tenth gradeSMK Mutiara Terpadu Palabuhanratu?. The type of this research was quantitatif throgh quasi experimental research which used control class and experimental class. The subject of this research was the 10th grade Farmasi as control class and 10th grade Perawat as experimental class. Data in the form of pre-test and post-test than analyzed quantitatif. In analyzing data, there was found N-Gain score and mean score of pre- test and post-tes. The N-Gain score of experimental class was about 60,92 with interpretation Moderately Effective. So it conclude that HelloTalk application has significant effect or moderately effective to improve writing skill in recount text, and the improvement of Students’ can be seen from the comparison means score of pre-test and post-test of experimental class. It increased 25% afte comparison, from 60,4100 to 85,0876. It assumed that Students’ grade increased after using HelloTalk application. The hypothesis of this research was computed by th T-test, where the result of the value of Asymp.Sig.(2-tailed) of 0.000